Criticality at the intersection of the curatorial and socially-engaged art practices in post-2000 Singapore - Juraimy Abu Bakar (Nanyang Technological University, 2022)
The tendency to employ art as a way of mediating prevailing social issues that perturbed society has always been a feature of Singapore artistic practices. This can be traced back to the days of the Malayan Emergency in Singapore, right up to the 1990s. Post-2000 Singapore witnessed a thriving art scene which became a conducive environment for socially-engaged curatorial and art practices to address complex social issues. Paying particular attention to key milestone developments that affected these two practices globally and regionally, this dissertation studies how the criticality of socially-engaged curatorial and art practices in post-2000 Singapore had not only been shaped by Singapore’s own social-historical-political conditions, but also the social turn in post-2000 Singapore arts policy-making. In reviewing also details of the Singapore Arts Plan, this dissertation interrogates the participation of the state in sociallyengaged art practices; and inquires the effects this has on assuring or challenging visibility, representation and agency, given the state’s tendency to respond to ‘disruptive’ works with suspicion. The dynamics of the situation compels curators and artists to practise their knowledge, skills and resources with greater 'political' agility and wisdom to avoid undermining representation and visibility as they navigate to manage arising tensions and opportunities at the intersection of practices. This dissertation is aiming for a critical approach to the study of the curatorial practice intersecting with socially-engaged art practices endorsed by the state.